Treatment of Tuberculous Meningitis With Contezolid in a Patient With Complex Comorbidities: A Case Report and Literature Review - Qi Fan; Hong Sun; Shengsheng Liu (Case Reports in Infectious Diseases)
Central nervous system (CNS) tuberculosis (TB) is a severe manifestation of Mycobacterium tuberculosis (MTB) infection, characterized by high mortality. Contezolid, a novel oxazolidinone antibiotic, exhibits in vitro activity against MTB and may offer a safety advantage over linezolid, a first-generation oxazolidinone frequently linked to myelosuppression and neuropathy. Clinical data on contezolid in CNS tuberculosis remain scarce. We report a middle-aged man with chronic renal allograft dysfunction who was receiving long-term hemodialysis and subsequently developed severe CNS TB complicated by multiple coinfections, diabetes mellitus, and pancytopenia. An individualized multidrug regimen that included contezolid was successfully employed, suggesting its potential utility in complex CNS TB. This report highlights therapeutic considerations for similar patients and underscores the need for further research on the role of contezolid in TB treatment.